Inequality in the Survival of Patients With Head and Neck Cancer in Scotland - Ingarfield, Kate; McMahon, Alex Douglas; Douglas, Catriona M.; Savage, Shirley-Anne; MacKenzie, Kenneth; Conway, David I. (Frontiers in Oncology, 2019)
Background: Socioeconomic inequalities impact on the survival of head and neck cancer patients, but there is limited understanding of the explanations of the inequality, particularly in long-term survival. Methods: Patients were recruited from the Scottish Audit of Head and Neck cancer from 1999 to 2001 and were linked to mortality data as at 30th September 2013. Socioeconomic status was determined using the area-based Carstairs 2001 index. Overall and disease-specific survival were calculated using the Kaplan-Meier method with 95% confidence intervals (CI’s) at one-, five- and 12-years. Cox proportional hazard models with 95% CIs were used to determine the explanations for the inequality in survival by all-cause mortality and disease-specific mortality with 95% CIs. Net survival at one-, five- and 12-years was also computed with 95% CIs. Results: Most patients were from the most deprived group, and were more likely to smoke, drink, have cancer of a higher stage and have a lower WHO Performance Status. A clear gradient across Carstairs fifths for unadjusted overall and disease-specific survival was observed at one-, five- and 12-years for patients with HNC. Multiple patient, tumour and treatment factors play a part in the inequality observed, particularly by five- and 12-years when the inequality could be explained in fully adjusted models. However, the inequality at one-year survival remained. The inequality in 12-year net survival was very small, suggesting that the inequality in the long-term may be partly attributable to background mortality. Conclusion: Explanations for the inequality in the survival of patients with HNC are not straightforward, and this study concludes that many factors play a part including multiple patient, tumour and treatment factors.